Supporting informed choice in acupuncture: effects of a new person-, evidence- and theory-based website for patients with back pain. Issue 2 (April 2019) - Bishop, Felicity L; Greville-Harris, Maddy; Bostock, Jennifer; Din, Amy; Graham, Cynthia A; Lewith, George; Liossi, Christina; O'Riordan, Tim; White, Peter; Yardley, Lucy
Objectives: To test whether a newly developed person-, theory- and evidence-based website about acupuncture helps patients make informed decisions about whether or not to use acupuncture for back pain. Methods: A randomised online study compared a newly developed 'enhanced website' to a 'standard website'. The enhanced website provided evidence-based information in a person-based manner and targeted psychological constructs. The standard website was based on a widely used patient information leaflet. In total, 350 adults with recent self-reported back pain were recruited from general practices in South West England. The two primary outcomes were knowledge change and making an informed choice about using acupuncture. Secondary outcomes were beliefs about and willingness to have acupuncture. Results: Participants who viewed the enhanced acupuncture website had a significantly greater increase in knowledge about acupuncture (M = 1.1, standard deviation (SD) = 1.7) than participants who viewed the standard website (M = 0.2, SD = 1.1; F(1, 315) = 37.93, p < 0.001, η 2 = .107). Participants who viewed the enhanced acupuncture website were also 3.3 times more likely to make an informed choice about using acupuncture than those who viewed the standard website (χ 2 (1) = 23.46, p < 0.001). There were no significant effects on treatment beliefs or willingness to have acupuncture. Conclusion: The enhanced website improved patients' knowledge and ability to make an informed choice about acupuncture, but did not optimise treatment beliefs or change willingness to have acupuncture. The enhanced website could be used to support informed decision-making among primary care patients and members of the general public considering using acupuncture for back pain.